Comparison of Muscle Cross-sectional Area and Lumbar Muscle Strength According to Degenerative Spinal Diseases - Ji-Hoon Cho; Ki-Hyuk Lee; Seung-Taek Lim; Buong-O Chun (Asian Society of Kinesiology, 2020)
OBJECTIVES The purpose of this study was to investigate the difference in the cross - sectional area (CSA) of multifidus and Iliopsoas muscles and the lumbar extension muscle strength according to degenerative spinal diseases (LHI; lumbar herniation of intervertebral disc group, SS; spinal stenosis group, S; spondylolisthesis group). METHODS The CSA of multifidus and Iliopsoas muscles size were measured by PACS(Picture Achiving and Communication System) using MRI at the L4/5 level and lumbar extension muscle strength (72˚, 60˚, 48˚, 36˚, 24˚, 12˚, 0˚) was measured using lumbar extension machine(MedX) in 97 patients of degenerative spinal diseases(male: 57, female: 40). The collected data were analyzed by one-way ANOVA using the SPSS program. RESULTS The results of this study showed that the CSA of total and right multifidus muscle in the LHI was significantly higher than that of the S (p <.05; p <.05) in the male group. The difference between the left and right CSA of multifidus in the LHI group was significantly higher than that of the SS (p <.05) in the male group (p <.05) and total group (p <.05). The CSA of iliopsoas muscle in the S was significantly higher than that of the LHI in the male and total group (p <.05; p <.05). In case of lumbar extension muscle strength, the S showed significantly higher muscle strength at 36 and 48 degrees than that of the SS in the male group. In the total group, LHI showed significantly higher muscle strength at 60 degrees of lumbar extension muscle strength than that of the S. CONCLUSION Multifidus muscle appears to be a key factor in prevention and treatment intervention in low back pain patients. In particular, in the case of S group, exercise therapy for strengthening the multifidus muscle is need for the rehabilitation.